Development of pH Sensing Devices Based on Optical Fluorescents with Rapid Measurement, Low Cost and Wireless Monitoring - Rahmat Fauzi Siregar; Totok Mujiono (JAREE (Journal on Advanced Research in Electrical Engineering), 2020)
The level of acid or base in water based on solution (pH) is a very important measure for living things because about 70% in the body consists of water. Most of the metabolism in the body requires a certain pH level. Having a rapid and accurate pH meter is very demanding, but most of the available pH meters take several minutes to measure the pH of the liquid. The measured water is mixed with fluorescent liquid and then excited with violet light at a wavelength of 405 nm. We have developed a pH meter based on optical fluorescent using pyranine extracted from yellow highlighter using isopropyl alcohol. The pH meter based on optical fluorescent have advantage compared to other methods in terms of measurement time. The intensity of the green fluorescent emitted from the liquid sample is then captured by the AS7262 spectral sensor. A pH sensing device has been developed, tested and verified to be able to measure pH from a range of 4 to 11 with an accuracy of 98.13%, a reading error value of ±0.13 and only takes less than 3 seconds to take measurements.Keywords: fluorescent, pH sensor, pyranine.